Could there Be a Synthesis between Western and Oriental Medicine, and with Sasang Constitutional Medicine in Particular?. (2009) - Noble, Denis
Abstract : Attitudes towards oriental medicine are changing for two major reasons. The first is that many patients, even in the West, are choosing to use its practitioners and methods. The second is that the rise of Systems Biology may offer a better basis for dialogue, and even for synthesis, between the oriental and Western traditions. However, a lot of work is needed to clear the way for such dialogue and synthesis. Much of this work should be devoted to clarifying the meanings of the terms used, and the framework of theory and practice within which oriental methods operate. But it is also necessary for Systems Biology itself to mature as a discipline, particularly at the higher levels of biological organization since it is at these levels that oriental medicine derives its ideas and practice. Higher level Systems Biology could be a basis for interpretation of the Korean version of oriental medicine: Sasang constitutional medicine since it seeks patient specific analysis and treatment, and the mathematical methods of systems biology could be used to analyze the central concept of balance in Sasang.